2021
DOI: 10.1097/j.jcrs.0000000000000608
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of first 50 cases using a new pupil expander

Abstract: The APX-200 was effective and safe device for pupil expansion during cataract surgery and IOL repositioning surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Fourteen eyes (28%) had mild sphincter tears that did not require pupilloplasty. No complication related to the use of the APX such as hyphema, iridodialysis, or Descemet membrane detachment were noted in this series [57] (video: https://www.aao.org/clinical-video/ apx-novel-pupil-expander and https://www.youtube.com/watch?v=3OvxfcjqrZQ).…”
Section: Assia Pupil Expander Devicesmentioning
confidence: 75%
See 1 more Smart Citation
“…Fourteen eyes (28%) had mild sphincter tears that did not require pupilloplasty. No complication related to the use of the APX such as hyphema, iridodialysis, or Descemet membrane detachment were noted in this series [57] (video: https://www.aao.org/clinical-video/ apx-novel-pupil-expander and https://www.youtube.com/watch?v=3OvxfcjqrZQ).…”
Section: Assia Pupil Expander Devicesmentioning
confidence: 75%
“…The APX provide a square pupil very similar to the four iris hooks; however, the number of incisions necessary to achieve pupil expansion is limited to two rather than four. Among potential advantages over expansion ring devices, no intracameral maneuvers are needed and the smaller profile might make this device more suitable for crowded anterior chamber [29,57,58]. A recent study has reported the outcomes of the first 50 consecutive eyes where APX-200 was used to enlarge small pupils, with mean preoperative pupil diameter of 3.7 mm.…”
Section: Assia Pupil Expander Devicesmentioning
confidence: 99%
“…Therefore, additional post-operative complications may be induced by iridoschisis, for example, the sphincter muscle can be damaged, and the pigmented iris epithelium can be exposed, thereby inducing symptomatic photic phenomena [19][20][21][22] . To protect the iris, several pupil expanding devices are conducive to the surgery, including iris retractors, flexible iris hooks, and pupil expanders [16,[23][24][25][26] . Among of which, iris hooks is commonly available in most operating room, while many surgeons habitually use the device for inadequate pupil dilation [27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…Iris hooks are more cumbersome, tedious, and timeconsuming [8,9]. With the availability of devices like the Malyugin ring, Canabrava ring, Assia pupil expander, B-Hex, I ring, and Iris speculum, among others, the threshold for using pupil augmentation rings has come down [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%